Expression of L-amino acid oxidase of Trichoderma harzianum in tobacco confers resistance to Sclerotinia sclerotiorum and Botrytis cinerea. (February 2021) - Peng, Kou-Cheng; Lin, Chao-Chi; Liao, Chong-Fu; Yu, Hsin-Chiao; Lo, Chaur-Tsuen; Yang, Hsueh-Hui; Lin, Kuo-Chih
Graphical abstract: Highlights: ThLAAO activates defense mechanisms via H2 O2 signaling. ThLAAO confers resistance against fungal pathogens. ThLAAO is translocated to leaves and targets chloroplast. ThLAAO binds to chlorophyll a /b binding protein. ThLAAO elicits systemic resistance against Botrytis cinerea. Abstract: L-amino acid oxidase (ThLAAO) secreted by Trichoderma harzianum ETS323 is a ﬂavoenzyme with antimicrobial characteristics. In this study, we transformed the ThLAAO gene into tobacco to elucidate whether ThLAAO can activate defense mechanisms and confer resistance against phytopathogens. Transgenic tobacco overexpressing ThLAAO showed enhanced resistance against Sclerotinia sclerotiorum and Botrytis cinerea and activated the expression of defense-related genes and the genes involved in salicylic acid, jasmonic acid, and ethylene biosynthesis accompanied by substantial accumulation of H2 O2 in chloroplasts, cytosol around chloroplasts, and cell membranes of transgenic tobacco. Scavenge of H2 O2 with ascorbic acid abolished disease resistance against B. cinerea infection and decreased the expression of defense-related genes. ThLAAO-FITC application on tobacco protoplast or overexpression of ThLAAO-GFP in tobacco revealed the localization of ThLAAO in chloroplasts. Chlorophyll a /b binding protein (CAB) was isolated through ThLAAO-ConA affinity chromatography. The pull down assay results confirmed ThLAAO–CAB binding. Application of ThLAAO-Cy5.5 on cabbage roots promptly translocated to the leaves. Treatment of ThLAAO on cabbage roots induces systemic resistance against B. cinerea. Overall, these results demonstrate that ThLAAO may target chloroplast and activate defense mechanisms via H2 O2 signaling to confer resistance against S. sclerotiorum and B. cinerea .